Hepatotoxicity caused by montelukast in a paediatric patient - Lebensztejn, Dariusz; Bobrus-Chociej, Anna; Kłusek, Monika; Uscinowicz, Miroslawa; Lotowska, Joanna; Sobaniec-Lotowska, Maria; Kaczmarski, Maciej (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Montelukast is a selective and competitive cysteinyl leukotriene receptor antagonist (CystLTRA) which is increasingly used for the treatment of allergic asthma. Recently, hepatotoxicity has been reported with this drug in adult patients, but only one letter to the editor has reported a case of probable montelukast-induced hepatotoxicity in a child. We present a case of a 3.5-year-old boy, receiving treatment with montelukast, who developed hepatocellular injury. The exclusion of other causes of increased activity of aminotransferases (viral, metabolic, autoimmune), improvement after dechallenge, the morphological findings and previous reports of comparable cases support the diagnosis of montelukast-induced liver injury in this boy. Physicians should strictly analyse indications for this drug and be aware of potential drug-induced liver disease caused by this agent. Therefore, the periodical assessment of aminotransferases should be recommended during treatment with this leukotriene modifier.